Recommendations for Therapeutic Apheresis by the Section "preparative and Therapeutic Hemapheresis" of the German Society for Transfusion Medicine and Immunohematology - Worel, Nina; Mansouri Taleghani, Behrouz; Strasser, Erwin (Transfusion Medicine and Hemotherapy, 2019)
The section "Preparative and Therapeutic Hemapheresis" of the German Society for Transfusion Medicine and Immunohematology (DGTI) has reviewed the actual literature and updated techniques and indications for evidence-based use of therapeutic apheresis in human disease. The recommendations are mostly in line with the "Guidelines on the Use of Therapeutic Apheresis in Clinical Practice" published by the Writing Committee of the American Society for Apheresis (ASFA) and have been conducted by experts from the DACH (Germany, Austria, Switzerland) region.
CRIS-Team Scopus Importer:2019-11-22